Interventional Pneumology in Pulmonary Bleeding; A Review: From the Bronchus to the Vessel. Issue 1 (1997) - Witt, Christian; Romaniuk, Paul; Schmidt, Bernd; Geisler, Anika; Klein, Katrin; Fietze, Ingo; Borges, Adrian Constantin; Liebers, Uta; Dörffel, Wolf; Baumann, Gert
Abstract : Interventional pneumology includes both bronchological and vascular methods of diagnosis and therapy, especially in emergency situations such as pulmonary hemorrhage. In massive pulmonary hemorrhage bronchological diagnosis is required to determine the site and extent of bleeding, as well as angiography of bronchial arteries, and of pulmonary arteries. Bronchus occlusion by aid of balloon catheter or double lumen tube are holding measures until definitive surgery or embolization of bronchial or pulmonary arteries can be performed. The paper suggests a close relationship between bronchoscopic and angiographic diagnosis and therapy in case of severe pulmonary bleeding.